(untitled) (MAUSAM, 1970)
More than 100 rainstorms of durations ranging from 2 to 7-day during the period 1901-1960 over the Brahmaputra catchment in Assam plains have been studied by the Isohyetal Method. Enveloping curves of maximam depths for various durations are presented and discussed in this paper. The synoptic situations associated with some of the heavy storms are also discussed.